Growth Differentiation Factor-15 (GDF-15) is a Biological Marker in Heart Failure - A. M. Alieva; E. V. Reznik; T. V. Pinchuk; R. A. Arakelyan; R. K. Valiev; A. M. Rakhaev; A. S. Tikhomirova; I. G. Nikitin (SINAPS LLC, 2023)
Heart failure is an important medical, social and economic problem around the world. In recent years, a number of diagnostic and prognostic biological markers of blood in cardiovascular diseases have been studied. Identification of new biological markers, analysis of their pathophysiological aspects and changes in concentration under the influence of various treatment options, allow us to understand many pathogenetic features of the development and course of heart failure. In recent decades, natriuretic peptides have been introduced into clinical practice, which are widely used as reliable markers for diagnostic and prognostic assessment. Growth differentiation factor-15 is a cytokine belonging to the family of transforming growth factors, the activity of which is significantly increased under stress and inflammation. In patients with chronic heart failure, the concentration of this marker is associated with an increased risk of overall mortality and adverse cardiovascular events; in patients with heart failure with preserved left ventricular ejection fraction, the use of the marker showed prognostic and diagnostic significance. Data from the Framingham Heart Study showed that growth differentiation factor-15 was the only marker in multivariate analysis that showed a statistically significant association with all adverse cardiovascular events. Eight studies showed that overexpression of growth differentiation factor-15 was associated with an increased risk of mortality in patients with heart failure. It was shown that growth differentiation factor-15 as a prognostic marker in patients with acute heart failure is not inferior to the brain natriuretic peptide precursor. To confirm the value of this marker in blood in patients with heart failure, it is necessary to conduct extensive prospective randomized clinical trials.